Institute of currency regulation and control in the Eurasian Economic Union - Galiullina, С.Д.; Suleimanov, А.Р. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The formation of the Eurasian Economic Union in the context of hyper competition and global cooperation is one of the most difficult stages in the integration of post-Soviet countries and implies the intensification of cooperation between the member states in several areas, while the issue of a coordinated monetary policy is given priority. The monetary policy of the EAEU, represented by currency regulation and control, is an important mechanism influencing the development of trade and economic relations and bringing its participants closer to common goals – the formation of common markets and systems of goods (services), finance, and energy resources. This article examines the process of institutionalization of currency regulation and control within the framework of the Eurasian integration association, priority areas, and constraints, and also proposes promising ways to modernize this process through the creation of a currency union within the framework of this integration association. Official data of the Eurasian Economic Commission, statistical services, large banks of the EAEU member countries, international trade, economic and foreign exchange organizations were used as sources of information for the analysis.Based on general scientific and special research methods, the authors reveal the processes of institutionalization of currency regulation and control, features of currency relations in the EAEU, draw conclusions about the specifics of the institution of currency regulation and control in the EAEU states, and also propose a scenario forecast of the prospects for currency integration within the EAEU.